Evaluating Forelimb and Hindlimb Joint Conformation of Morna Racehorses (Equus caballus) - Israr Ahmad; Sahar Ijaz; Mirza M. Usman; Ayesha Safdar; Imdad U. Khan; Muhammad Zeeshan; Syed S. U. H. Bukhari (Veterinary Sciences)
Measuring limb joint angles is crucial for understanding horse conformation, performance, injury diagnosis, and prevention. While Thoroughbred horses have been extensively studied, local Pakistani breeds (e.g., Morna racehorse) have not received scientific attention. This study aimed to quantify normal angles of limb joints in the Morna breed. Limb joint angles of standing horses (n = 50) were quantified using a measuring tape, height stick, protractor scale, and goniometer. The mean and standard deviation (Mean ± SD) values for the forelimb joint angles were 123.02 ± 3.46° for elbow, 171.52 ± 2.39° for knee, and 147.68 ± 5.11° for fetlock. The mean ± SD values for the hindlimb joint angles were 128.62 ± 4.08° for stifle, 160.40 ± 3.89° for hock, and 155.48 ± 2.68° for fetlock. There was a non-significant (p > 0.05) correlation between horse joint angles and, age, body weight, and body condition score (BCS). The elbow and stifle joint angles of Morna align well with characteristics associated with optimal racing performance. However, the hock and fetlock angles differ from jumping Thoroughbred and French trotters. We recommend further research to examine the conformation of the Morna breed, particularly by measuring the lengths of limb segments and correlating it with joint angles. This may provide valuable insights into individual variations within the breed.